Using surface markers to describe the kinematics of the medial longitudinal arch in a longitudinal study of flexible flat feet and health-related quality of life - Uhan, J (2023)
Flexible flat foot (FFF) is a condition which, despite being commonly seen in the clinical setting, has no clear consensus on its aetiology, prognosis, or management plan. This thesis aimed to observe the natural development of the medial longitudinal arch (MLA) from childhood into adulthood in in FFF and compare it with neutral feet (NF). This is the first known longitudinal study of FFF. To conduct this study, it was initially necessary to develop a measure to characterise the MLA accurately and reliably in both static and dynamic stances. This entailed the comparison of eight configurations of motion-capture markers on the foot. Each configuration used varying combinations of real and virtual foot marker coordinates to enable measurement of the MLA angle. The optimal MLA measure was selected based on quantitative and qualitative Multi Criteria Decision Analysis, criteria for which were determined through a Delphi study. The measure which used real markers on the heel, navicular, and first and fifth metatarsal heads, was determined as the best choice for assessing the MLA. Initially, it was applied to participants with cerebral palsy, to observe if it could characterise the MLA in feet with complex deformity and variable walking patterns. This demonstrated good alignment with established measures of the foot, as well as with clinical observation of foot behaviour. Therefore, it was deemed suitable for comparing the static foot posture and walking patterns of participants with FFF and NF between childhood and adulthood. In addition, the effect of FFF in childhood on quality of life (QofL) in adulthood was assessed, to help decide which feet should be treated. Overall, the MLA for the FFF group did not improve over time, suggesting these feet do not spontaneously resolve. There was some evidence to suggest children with FFF may have poorer QofL outcomes in adulthood. In particular, limitations in forefoot supination and hindfoot dorsiflexion may be predictors of poorer QofL in adulthood.